Analisis Kemampuan Literasi sains Peserta Didik Kelas VIII SMPN di Kecamatan Polewali - Yuni Zulfaeni Amri; Hasanuddin Hasanuddin; Sitti Rahma Yunus (Celebes Science Education, 2024)
This study aims to determine how high the level of ability of science literacy competency aspects of class VIII students in Polewali District. This research is a descriptive survey research using a quantitative approach. The population in this study were students of grade VIII junior high school in Polewali District as many as 745 students from 3 schools namely SMPN 1 Polewali, SMPN 3 Polewali and SMPN 4 Polewali. Sampling using Random Sampling technique and determining the number of samples using the slovin formula which is 286 students. The research instrument was a multiple choice question of 20 items. Based on the results of data analysis, it is known that the level of ability of science literacy competency aspects of VIII grade students in Polewali District is 48.23% which is included in the low category.